1992
DOI: 10.1016/s1056-4993(18)30601-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parent Training Groups in the Treatment of Attention-Deficit Hyperactivity Disorder

Abstract: Article:Within the fields of child development and child clinical psychology, recognition is growing of the important role that families, in particular parents, play in the growth and development of children. Compared with a simplistic unidirectional view, researchers and clinicians increasingly have conceptualized parent-child influences from a more realistic transactional pattern 14,15,62 or a systems perspective. 45 For example, developmental researchers such as Baumrind, 12 Maccoby and Martin, 42 and Schae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It can also positively impact quality of life by increasing effective parenting skills and parent understanding of their child’s NDD, and reducing parent stress [ 33 , 54 , 55 ]. More specifically, a number of studies have demonstrated that parental stress can be reduced and the whole family environment can be improved by increasing parental skills to improve their child’s condition [ 45 , 56 , 57 ]. Parent-mediated programmes have been found to be cost effective in high income countries (HIC) and are recommended as a means of sustainable support for children with NDDs [ 56 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can also positively impact quality of life by increasing effective parenting skills and parent understanding of their child’s NDD, and reducing parent stress [ 33 , 54 , 55 ]. More specifically, a number of studies have demonstrated that parental stress can be reduced and the whole family environment can be improved by increasing parental skills to improve their child’s condition [ 45 , 56 , 57 ]. Parent-mediated programmes have been found to be cost effective in high income countries (HIC) and are recommended as a means of sustainable support for children with NDDs [ 56 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Arnold et al, 1997;Hinshaw, Klein, & Abikoff, 1998;Pelham, Wheeler, & Chronis, 1998). Some studies have shown that PT programs for ADHD children positively impact on improving some aspects of the children's behavior (Newby, Fisher, & Roman, 1991;Pisterman et al, 1989;Shelton & Barkley, 1992). Other studies have examined whether PT programs combined with other traditional treatment approaches yield more favorable results (Cousins & Weiss, 1993;Firestone, Kelly, Goodman, & Davey, 1981;Horn et al, 1991;Ialongo et al, 1993).…”
mentioning
confidence: 99%